ANALISIS MINAT MEMBACA SISWA DI KELAS TINGGI SD YPK KLASAMAN 2 KOTA SORONG - Clara Angelin Maless; Abdulrahman Hatsama; Abdul Hafid (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This This research is motivated by the phenomenon of interest in reading in class 4 A students. This research aims to describe the conditions and what factors inhibit and support students' interest in reading in class 4 A at SD YPK Klasaman 2, Sorong City. The method used in this research is a qualitative method with a research design, namely a case study. The subjects in this research were the class teacher and 22 students in class 4 A of YPK Klasaman Elementary School, Sorong City. Data collection techniques in this research used interviews and observation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of this research indicate that the condition of students' interest in reading is good. This can be seen from the enthusiasm of the students in carrying out reading activities for 15 minutes before the lesson takes place or ends later during free time. The students fill the free time by reading textbooks and non-lessons in their respective seats, both in the library and in the classroom. Then, researchers found that there were several inhibiting factors, namely: There were still two students who could not read, there were no reading corners in each class except in the library, there was a lack of role and support from some parents. Supporting factors are the role and support of the teacher and most of the parents, then the teacher carries out reading activities for 15 minutes using textbooks or non-textbooks available in the library or student handbooks and there is great enthusiasm from the students.